Application of Bootstrap Simulation and Asymmetric Causal Approach to Fiscal Deficit-Inflation Nexus. (May 2020) - Olalekan Olaniyi, Clement
This paper investigates the symmetric and asymmetric relationship between fiscal deficits and inflation in Nigeria within the context of bootstrap simulations with leverage adjustments using the quarterly frequency data from 1981Q1 to 2016Q4. The findings reveal that there is neither symmetric nor asymmetric causality between fiscal deficits and inflation in Nigeria. This implies that the fiscal deficits in Nigeria are not inflationary; and also, that persistent double-digit inflation rates are not the causal agents spurring perennial increase in fiscal deficits in Nigeria. This study, therefore, concludes that fiscal deficits could be used to stimulate output level in Nigeria without fueling inflationary spiral in the economy. JEL Classification: C32, E17